CRISIS NETWORKS AND EMERGENCY BEHAVIOR: DIGITAL TECHNOLOGIES AND NON-STATE POLITICAL ACTOR ENGAGEMENT - ÜNVER, H.Akın (Cyberpolitik Journal, 2016)
The goal of this paper is to offer a new framework for conceptualizing the relationship between traditional channels of political expression and their adoption of emerging communication technologies to respond to the new challenges of digital crises. In doing so, it revisits the question “Are Digital Technologies Making Politics Impossible?”, approaching the questions from a non-state actor point of view. The paper offers a new view on the significance attributed to new digital technologies in collective action and the importance of how older and pre-existing networks adapt to technology during crisis mobilization, armed conflict, and protest. Scholars working to explain the impact of social movements have emphasized the importance of communicative technologies, especially media and the Internet. For sociologists and political scientists, explanations centered on political communication make sense, and the importance of connective action is widely accepted. Yet the connection between traditional and pre-existing mobilization networks, such as religious congregations, political parties, armed groups, and refugees, and modern digital communication technologies has not been well-established.